Patient care in Ayurveda with perspective to nursing: A Review - Acharya, Anita; Singh, Binod Kumar; Bhusal, Nirmal; Acharya, Sunita (Journal of Ayurveda Campus, 2024)
Background: Nursing encompasses care of individuals of different ages, families, groups, and communities who are healthy and sick in all settings. It includes promotive, preventive, curative, and rehabilitative care of ill, disabled, and dying people. Ayurveda, a science of life, is an ancient health care system practiced in the Indian subcontinent. With advancements in the Western medical system, there are increasing complexities, such as being expensive and technology dependent, whereas the traditional medical system is preferred for having a holistic approach. Material and Methods: This is a conceptual review. References regarding the Paricharaka have been collected, and relevant materials were compiled from various available Ayurveda classical texts like Charak Samhita, Sushruta Samhita, and Ashtanga Hridya, along with their commentaries and various text books of nursing. The information from various online published literatures regarding the concept of nursing was searched on Google Scholar, PubMed, Scopus, DOAJ, and ScienceDirect using key words such as “Ayurveda nursing,” “Ayurveda attendant,” “Ayurveda and nursing,” “nursing in traditional medicine,” “Paricharaka”, “Upasthata”, “TCM and nursing,” “Complementary and Alternative Medicines (“CAM”), and “nursing.” The concept of Paricharaka has been reorganised and critically analysed, and a conclusion was drawn. Results and Discussion: Ayurveda advocates four different components necessary for providing quality healthcare, termed Chikitsa Chatushpada. The components are Bhishaka (doctor/physician), Dravya (medicine), Upasthata (attendant/helper), and Rogi (patient). The description of each component has been mentioned in Samhitas. Ayurveda has documented the concept of nursing care. Nursing care was provided by traditional caretakers and Paricharaka in Ayurveda for years in tradition. Several classical texts have described the word Upasthata or Paricharaka within the context of treatment modalities. The words “Upasthata” and “Paricharaka” can be correlated with the nurse in Western medicine. The qualities of Upasthata or Paricharaka (nurse/attendant) are Buddhiman (intelligent), Daksha (skilled), Anurakta (affectionate), and Suchi (pure/clean). Conclusion: The concept of nursing care for patients can be traced back to the ancients, with a description of Chikitsa Chatuspada in the Samhitas of Ayurveda. It is one of the Chikitsa Chatuspada, that is, “Upasthata” or “PParicharaka” who must be intelligent, skilled, affectionate, and neat and clean. The qualities of Paricharika resemble those of nurses in the Western healthcare system.